Site amelioration for direct seeding of Caladenia tentaculata improves seedling recruitment and survival in natural habitat - Wright, Magali (Universidad de Costa Rica, 2015)
The genus Caladenia contains the largest number of threatened orchid species in Australia and improv- ing the success of re-introductions would allow exist- ing populations to be strengthened and new popula- tions to be established. Batty et al. (2006) showed that direct seeding of C. arenicola Hopper & A.P. Br. into habitat soil inoculated with mycorrhizal fungus resulted in a good in situ germination rates.